Assessing how metal reef restoration structures shape the functional and taxonomic profile of coral-associated bacterial communities - Strudwick, Paige; Suggett, David J.; Seymour, Justin R.; DeMaere, Matthew Z.; Grima, Amanda; Edmondson, John; McArdle, Alicia; Nicholson, Freda; Camp, Emma F. (Frontiers in Marine Science, 2024)
Significant threats to the long-term persistence of coral reefs have accelerated the adoption of coral propagation and out-planting approaches. However, how materials commonly used for propagation structures could potentially affect coral-associated bacterial communities remains untested. Here, we examined the impact of metal propagation structures on coral-associated bacterial communities. Fragments of the coral species Acropora millepora were grown on aluminium, sand/epoxy-coated steel (Reef Stars), and uncoated steel (rebar) structures. After 6 months, the functional and taxonomic profiles of coral-associated bacterial communities of propagated corals and reef colonies were characterised using amplicon (16S rRNA gene) and shotgun metagenomic sequencing. No differences in the phylogenetic structure or functional profile of coral-associated bacterial communities were observed between propagated corals and reef colonies. However, specific genes and pathways (e.g., lipid, nucleotide, and carbohydrate metabolism) were overrepresented in corals grown on different materials, and different taxa were indicative of the materials. These findings indicate that coral propagation on different materials may lead to differences in the individual bacterial taxa and functional potential of coral-associated bacterial communities, but how these contribute to changed holobiont fitness presents a key question to be addressed.